Influence of Elevation on Falcataria moluccana [Miq.] Barneby & J.W. Grimes Gall Rust Incidence and Severity in Agusan del Norte, Philippines - Tering, Rece Ruby Gera; Branzuela, Nympha Ellarina; Batiancela, Marvin Arroyo; Tutor, Rosalinda Palo (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
Gall rust disease poses a significant threat to falcata (Falcataria moluccana [Miq.] Barneby & J.W. Grimes), particularly in different elevation ranges. This study aimed to assess the gall rust disease incidence and severity at low (0–200 masl), moderate (201–400 masl), and high (401–600 masl) elevations. Results showed a significant correlation between gall rust disease incidence and severity and elevation based on Spearman rho correlation analysis. Higher elevations were associated with increased gall rust disease incidence and severity. This suggests that environmental conditions specific to these elevations may aggravate gall rust development. Based on the findings, temperature and relative humidity, which vary with elevation, play a role in gall rust disease incidence. Conversely, light intensity significantly influences gall rust disease severity across elevation ranges. These findings signify the importance of elevation-related factors in disease management strategies in falcata plantations. By identifying the relationship between gall rust disease and elevation, this research provides insightful information that can be used to improve disease management strategies and create focused control measures. The results provide an in-depth understanding of gall rust disease dynamics and offer recommendations for reducing its impact. Keywords: disease incidence, disease severity, elevation, Falcataria moluccana, gall rust